Reflections on Student Learning and Discernment in a Service-Learning Course - Storms, Stephanie Burrell; Calderwood, Patricia; Quan, Melissa (International Journal of Research on Service-Learning in Teacher Education, 2018)
This study focuses on short-term learning outcomes for university students across multiple sections of one pre-professional service-learning course, foregrounding their immediate experience within the complex ecology of the partnership. Findings inform ongoing adjustments to the partnership design, and influence design of developmental outcomes in a five-year teacher education program in elementary and secondary education, with regard to reflective practice, sense of self in relation to diversity, civic and social awareness and engagement, and struggling with and reconciling emerging conceptions of social justice.